Early North African Acheulean techno-economic systems at Thomas Quarry I -L1 (Casablanca, Morocco) - (:unkn) unknown (My University, 2023)
North Africa is a key area for understanding cultural processes that led to the Acheulean pan-African emergence and expressions and the related hominin population dynamics. Unfortunately, little is known about the early Acheulean in this vast area of the African continent due to the scarceness of archaeological sites in stratigraphic context with reliable chronometric data, human remains, and technological analyses of the lithic industries. Here, we present the first comprehensive techno-economic analysis of the early Acheulean assemblage from Thomas Quarry I-Unit L1 (ThI-L1, Casablanca, Morocco), which is the earliest Acheulean site of North Africa, unambiguously dated to 1.3 Ma. Fieldwork has unearthed faunal remains and a lithic collection containing over 3800 artefacts, which represents one of the largest series for the early African Acheulean. The assemblage is mainly composed of quartzites and to a lesser extent of silicites, both abundantly available near the site. Previously published results of the silicite study revealed two different productions for the extraction of small flakes and of bladelet-like flakes. In this work, we analyse the techno-economic systems of the quartzite assemblage. Two distinct quartzite productions co-occur, one devoted to the manufacture of Large Cutting Tools (LCTs), the other focused on the extraction of small-medium sized flakes. LCTs were usually produced from large cobbles, less often from large flakes detached mainly using the entame core method. The main technical objective was to obtain large pointed tools and, more rarely, large tools with a transversal cutting edge. Results support the existence of a strong synergy between conceptual and operational schemes regulated by the ability to anticipate the final tool morphology and to apply standardized shaping procedures to manufacture recurrent morphotypes. Quartzite small-medium sized flakes were produced by a diversity of flaking methods adapted to the cobble
Keywords: African Research